THE EFFECT OF ROLE PLAYING METHOD TOWARD THE ABILITY OF FICTION READING COMPREHENSION OF HEARING IMPAIRMENT STUDENT - Wahyuningtyas, Lestari; Susilawati, Sinta Yuni (Department of Special Education, 2016)
This research was carried out with the aim at describing: (1) the ability of fiction reading comprehension of student with hearing impairment of grade VIII at SMPLBN Malang before and after being applied role playing method, (2) the effect of role playing method toward the ability of fiction reading comprehension of student with hearing impairment of grade VIII at SMPLBN Malang. This study used quantitative research design with Single Subject Reserch Method (SSR) of A-B-A design. Based on the analysis, it was obtained the following results. On baseline-1 showed that the ability of fiction reading comprehension of students was low. On the intervention phase showed that the ability of fiction reading comprehension improved, if it was compared to the mean level in baseline-1. In baseline 2 phase showed that the ability of fiction reading comprehension was dropped.